Selection the mechanism of evolution - Bell, Graham, 1949- (Oxford : Oxford University Press, 2008)
This text adopts a direct experimental approach to evolutionary questions, drawing predominantly from research on microbial systems. The focus is on processes and mechanisms, and incorporates insights from recent advances in whole-genome sequencing, bioinformatics, environmental genomics and developmental genetics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural selection; Evolution (Biology)